2021
DOI: 10.1007/s12265-021-10151-7
|View full text |Cite
|
Sign up to set email alerts
|

A Machine Learning Methodology for Identification and Triage of Heart Failure Exacerbations

Abstract: Inadequate at-home management and self-awareness of heart failure (HF) exacerbations are known to be leading causes of the greater than 1 million estimated HF-related hospitalizations in the USA alone. Most current at-home HF management protocols include paper guidelines or exploratory health applications that lack rigor and validation at the level of the individual patient. We report on a novel triage methodology that uses machine learning predictions for real-time detection and assessment of exacerbations. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The models developed obtained an S of 76 to 88% and an E of 85%, values similar to those of the models in our study. Recently, Morrill et al 30 reported diagnostic models of decompensated HF developed with ML techniques with an S of 100% and E of 73% but based on simulated clinical situations and not real patients.…”
Section: Resultsmentioning
confidence: 99%
“…The models developed obtained an S of 76 to 88% and an E of 85%, values similar to those of the models in our study. Recently, Morrill et al 30 reported diagnostic models of decompensated HF developed with ML techniques with an S of 100% and E of 73% but based on simulated clinical situations and not real patients.…”
Section: Resultsmentioning
confidence: 99%
“…The models developed obtained an S of 76 to 88% and an E of 85%, values similar to those of the models in our study. Recently, Morrill et al 33 reported diagnostic models of decompensated HF developed with ML techniques with an S of 100% and E of 73% but based on simulated clinical situations and not real patients.…”
Section: Resultsmentioning
confidence: 99%
“…Telehealth provides support for adequate hospital visiting (Hollander and Carr, 2020;Sivarajasingam, 2021). In fact, several studies have reported that an online strategy provided effective support for adequate hospital visiting for emergency patients and patients with burns, heart failure, and cervical cancer (Arrossi et al, 2019;Carmichael et al, 2020;Chai et al, 2021;Beyer et al, 2022;Morrill et al, 2022). A study that conducted telemedicine screening assessments on four diagnostic cohorts-patients with gastroenteritis, psychiatric conditions, burn, or fractures-reported that the median doorto-provider times were reduced through telemedicine screening (Friedman et al, 2021).…”
Section: Introductionmentioning
confidence: 99%